Indications and techniques for robotic pelvic and para-aortic lymphadenectomy with sentinel lymph node mapping in gynecologic oncology. (November 2017) - Wisner, Ketura Preya A.; Ahmad, Sarfraz; Holloway, Robert W.
Abstract : Robotic-assisted laparoscopic surgery is the most common approach for the treatment of early-stage endometrial and cervical cancers in the US. Surgical staging requires pelvic and often aortic lymphadenectomy, depending on the primary tumor characteristics. Pelvic and aortic lymphadenectomy procedures may also be indicated for debulking of larger metastases to improve disease control. The infra-renal basin is an important anatomic site of metastasis from pelvic tumors, and robotic dissection techniques for this site have been described. In recent years, sentinel lymph node (SLN) mapping has been adopted into the National Comprehensive Cancer Network guidelines' surgical algorithm for uterine and cervical cancers. SLN mapping has higher sensitivity for the detection of nodal metastasis, despite removing fewer lymph nodes, and potentially reduces morbidities such as lower extremity lymphedema. This article reviews current robotic pelvic and para-aortic lymphadenectomy dissection techniques for endometrial and cervical cancers and discusses the recent integration of pelvic SLN mapping in the surgical algorithm. Highlights: The majority of uterine and cervical cancers are managed robotically in the US. Robotic pelvic and aortic lymphadenectomy is integral for FIGO staging. SLN mapping increases the detection of metastasis in uterine and cervical cancers. ICG has increased the detection of SLNs compared to blue dye.